Doing research in social work and social care : the journey from student to practitioner researcher - Flynn, Catherine; McDermott, Fiona, author (London : SAGE Publications Ltd, 2016)
This book guides students to becoming researchers by detailing the concepts of research and gathering data, to writing it all up and sharing knowledge to students
Research in the professional practice context -- Frameworks underpinning research -- Researching ethically: 'what you do is important but how you do it is more important' -- Arriving at a research question: building on existing knowledge -- Research design: shaping your study -- Selecting and accessing data: ensuring rigor -- Speaking and listening: interviews, focus groups and community forums -- Counting and measuring: questionnaires, scales and secondary analyses -- Making meaning from data: qualitative analysis -- Making meaning from data: quantitative analysis -- Writing and sharing your findings: creating knowledge for practice
Includes bibliographical references and index.
Keywords: Social service -- Research